Optimization of operation of the Mindanao power system - Lopez, Patricia L.
Basically, the Mindanao Power System is a water resource system because it is dominated by hydro plants. The operation of the reservoirs, of these plants, determines, the ability of the grid to deliver the energy required by its consumers at a cost that is efficient to its owner, in this case, the Government. In other words, system operation is equated to the management of these reservoirs. The effectivity of management is reflected in the absence of power failures resulting from low inflow and depleted reservoirs. Since inflow is an unknown quantity in the reservoir management, there is a need to plan for the reservoir releases which will affect the operation of the system. In recent years too much emphasis has been placed in the developmental planning of generation projects. Equally important however, is the planning for operation which aims for the efficient utilization of the system's energy resources, to minimize cost of operation, without sacrificing the ability of the system to deliver energy, at an acceptable degree of reliability. The ultimate goal of operations planning is optimization of all the reservoirs in the system on real time. Before a short term or real time optimization is achieved however, the long/middle term targets should be established to serve as inputs on the real time analysis. Thus, a logical step by step process shown as Fig. 19 and recommended in Chapter IX is necessary for a comprehensive approach to system optimization. This work is a first step towards the development of a real time optimization model of the Mindanao System and thus is centered on a long/middle term optimization analysis. The long/middle term optimization model developed, utilized an operations research method called the Dynamic Programming Successive Approximation (DPSA) technique. The objective function is the use of water from the reservoirs of the existing hydro plants to satisfy energy system requirements with the view to minimizing operating system cost through the minimum usage of the standby diesel plans over a 52-week or one-year period. The reliability criteria is expressed in monetary terms as Penalty if the reservoir is not able to meet end level targets. The result of the optimization process is an optimum policy - a schedule of releases with their corresponding reservoir levels which could serve as targets for future work on short term optimization. The study of the results will also provide an insight on system needs. The optimum policy is tested for reliability using a simulation software program (HEC-3) already available in NAPOCOR.